Explicit analysis using time-dependent damping simulation of one-sided laser shock peening on martensitic steel turbine blades. (December 2020) - Fameso, Festus; Desai, Dawood
Down-times from the in-service failure of power plant components, such as turbine blades, portend dire impacts and consequences in the form of huge financial losses. The susceptibility of steam turbine blades to failure is now being reduced by a novel technique, laser shock peening (LSP), which induces compressive layers through the surface of the blades. Current simulation studies of LSP employing conventional methods are indeed computationally expensive and time-consuming. Hence, this paper explores an alternative numerical modeling technique to investigate the economic parameters of residual stresses induced in martensitic steel turbine blades when subjected to LSP treatment. An explicit simulation method of analysis, using commercial finite-element software, which employs time-dependent damping, is presented. The study shows that this technique is time-efficient compared with the conventional explicit-implicit methods commonly used for such simulations. It is interesting to note that the results indicate that up to 500 MPa of induced compressive stress of layers reaching 1 mm in depth can be obtained. Encouragingly, these results correlate well with previous experimental studies, lending credence to the method's validity. The technique employed hence offers solutions for timely, non-destructive, methodical maintenance and improvement of the mechanical properties of turbine blades, in the quest to reduce the risks of their in-service failure, as well as lengthening of their service life.